A Simulation Method for Millimeter-wave Radar Sensing in Traffic Intersection Based on Bidirectional Analytical Ray Tracing Algorithm - Zong, Ming; Zhu, Zhanyu; Wang, Huaisheng (IEEE sensors journal, 2023)
Millimeter-wave (mmw) radar is indispensable for intelligent transportation systems (ITS), which can monitor traffic conditions in all weathers. An end-to-end simulation method for mmw radar monitoring and identification at traffic intersections is proposed in this paper. In this method, a virtual intersection scenario model is constructed, and the scattering coefficient of the target is calculated using the bidirectional analytical ray tracing (BART) algorithm. Combined with the generation of time-domain waveforms, the operation of frequency-domain convolution is simplified by inverse Fourier transform, and the echo signals received by the sparse array are simulated. After raw signal processing, point cloud images containing target position information and range-Doppler map (RDM) containing target state feature are obtained. The performance of mmw radar in detecting the specific location information of the target is evaluated by analyzing point cloud images. In addition, a self-defined convolutional neural network is introduced to evaluate the object recognition performance of the RDM. After the training of the neural network, the classification accuracy of this method for four types of vehicle targets can reach 92%.